2011
DOI: 10.1176/appi.ajp.2010.10101411
|View full text |Cite|
|
Sign up to set email alerts
|

Interpersonal Psychotherapy for Depression: A Meta-Analysis

Abstract: Objective Interpersonal psychotherapy (IPT), a structured and time-limited therapy, has been studied in many controlled trials. Numerous practice guidelines have recommended IPT as a treatment of choice for unipolar depressive disorders. The authors conducted a meta-analysis to integrate research on the effects of IPT. Method The authors searched bibliographical databases for randomized controlled trials comparing IPT with no treatment, usual care, other psychological treatments, and pharmacotherapy as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
221
2
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(254 citation statements)
references
References 72 publications
14
221
2
11
Order By: Relevance
“…The control regimen for IPC was an empirically validated high-intensity treatment modality, interpersonal psychotherapy (IPT) (Cuijpers et al, 2011;Markowitz & Weissman, 2012). In order to assess the benefits of a therapy method, one should design the control therapy so that it is similar in all other respects (e.g.…”
Section: Interventionsmentioning
confidence: 99%
“…The control regimen for IPC was an empirically validated high-intensity treatment modality, interpersonal psychotherapy (IPT) (Cuijpers et al, 2011;Markowitz & Weissman, 2012). In order to assess the benefits of a therapy method, one should design the control therapy so that it is similar in all other respects (e.g.…”
Section: Interventionsmentioning
confidence: 99%
“…Since the 1970s, several hundreds of randomized trials have shown that these interventions are effective [11][12][13][14] , although their effects are modest and have been overestimated because of the low quality of many trials 15 and publication bias 16,17 . The effects of psychotherapies have been found to be comparable to those of pharmacotherapy 18 , and probably last longer 19 .…”
mentioning
confidence: 99%
“…In a large RCT, Elkin et al (1989) found that IPT is equally effective to medication and CBT, with some evidence for increased efficacy of IPT for severely depressed patients. There is also preliminary evidence suggesting the superiority of IPT over alternative psychotherapies (Cuijpers et al 2008(Cuijpers et al , 2011, specifically supportive counselling (Barth et al 2013) and CBT (de Mello et al 2005).…”
Section: Interpersonal Therapy (Ipt)mentioning
confidence: 99%